Pola Asuh Orang Tua Keturunan Etnis Tionghoa dalam Memberikan Pengarahan Kepada Generasi Berikutnya di Kabupaten Ciamis - Desril Riva Shanti; Indra Riadi; Arif Saeful Bahri (PANALUNGTIK, 2023)
Ethnic Chinese are a minority community group in Ciamis. Its existence can be seen through the inheritance of existing culture. However, not all Ethnic Chinese families carry out cultural inheritance as they should. This is related to the differences in parenting patterns applied by each family. The purpose of this study is to determine the parenting patterns of ethnic Chinese parents in Ciamis. The method in this research is a qualitative research method. The concept used is the concept of culture according to Koentjaraningrat, that society is a complex system consisting of parts that are interconnected and dependent on each other, and each part has a significant effect on the other parts. The results showed that there are three types of parenting patterns: democratic, authoritarian, and permissive. In this study, it was found that totok Chinese families tend to use authoritarian parenting, while lower middle class peranakan Chinese families tend to use permissive parenting, and upper middle class peranakan Chinese families use democratic parenting.